IMOBILISASI DIFENILKARBAZIDA PADA SILIKA GEL DARI ABU SEKAM PADI MELALUI TEKNIK SOL GEL - Sari, Lestina; Sudiarta, I Wayan; Bawa Putra, Anak Agung (Jurnal Kimia (Journal of Chemistry), 2015)
The research was conducted to observe diphenylcarbazide immobilization on silica gel from rice husk ash (Si-CPTMS-DPZida) with sol-gel technique. The aim of this research was to modify silica gel from rice husk ash by immobilization with diphenylcarbazide using sol-gel technique. This research included the modification and characterization of silica gel. The characterizations of silica gel were done by using infrared spectrophotometer (FTIR) and X-ray diffraction (X-RD). The results showed that the immobilized diphenylcarbazide silica has been formmed which is indicated by the appearance of Si-OH functional group in the peak at wave number 914,26 cm -1 , Si-O-Si at 1091,71 cm -1 , the stretching vibration of NH group at 3645 cm -1 and proved in 1492 cm -1 which is the bending vibrations of the NH group, CH (aromatic) at  802.39 cm -1 , vibrational bending C = C (aromatic) at 1612 cm -1 , vibration CN group at 1310 cm -1 , and the vibrations of the C = O group in the area of 1685 cm -1 . The X-RD data showed that the structure of Si-CPTMS-DPZida is amorphous.
Keywords: immobilization, silica gel, diphenylcarbazide, sol-gel